Manajemen Pemasaran Perguruan Tinggi: Analisis Komparatif PTS di Banten Era Disrupsi: Higher Education Marketing Management: Comparative Analysis of PTS in Banten in the Era of Disruption - Ahmad Qurtubi (ITScience (Information Technology and Science), 2025)
Competition between private universities (PTS) in the era of disruption is getting tighter with the development of digital technology. This study analyzes the marketing strategies implemented by Syekh-Yusuf Islamic University (UNIS), Muhammadiyah University of Jakarta (UMJ), Nusantara Islamic University (UNISMA), and Mathla'ul Anwar University (UNMA) in facing marketing challenges in the digital era. This study uses a descriptive-comparative method with a qualitative and quantitative approach. The importance of this study lies in identifying the best strategies that PTS can implement to increase the competitiveness and sustainability of their institutions. This study provides insight into the effectiveness of the strategies implemented by UNIS, UMJ, UNISMA, and UNMA. It fills the research gap related to comparing PTS marketing strategies in the Banten region. Through this study, it is hoped that private universities in Banten can adapt marketing strategies that are more relevant, competitive, and by the demands of the times. The results of this study can also be a reference for policymakers in designing higher education policies that are more inclusive and responsive to global change. The results show that UNIS and UMJ are superior in utilizing social media compared to UNISMA and UNMA. UNIS uses artificial intelligence (AI) to customize marketing content personally, while UMJ adopts interactive webinars.In contrast, UNISMA and UNMA still rely on conventional methods that are less effective. The data shows that UNIS has the highest social media interaction (7.5%), followed by UMJ (6.8%), while UNISMA and UNMA are lower, 3.2% and 2.5%, respectively. In conclusion, digital marketing strategies provide a competitive advantage for PTS. Universities that still rely on conventional methods must immediately transform digitally to remain relevant and competitive in the increasingly dynamic higher education industry.